Enhancing English Learning through Teacher-Facilitated Study Groups: A Qualitive Study in Senior High School Level - Astutik, Yuli; Dewi, Yuni Lusiana; Fadhilah, Auliyah Nur; Suyoto, Shinta Widiowati; Ahsan, Ava Kenji (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the role of teachers in facilitating English learning through group study, emphasizing that teachers are pivotal in shaping students' abilities. Group learning techniques enhance engagement and teamwork, fostering a dynamic classroom environment that promotes academic, social, and cognitive growth. This qualitative research, conducted with thirty students from SMA Muhammadiyah 2 Sidoarjo's classes X1–5 and their English teachers during the 2023/2024 academic year, employed observations and interviews to gather insights. The study focused on cooperative learning and study groups to enhance classroom speaking activities. Findings revealed that the group learning approach, led by teachers, significantly improved students' English speaking, writing, reading, and comprehension skills. Active participation in study groups boosted students' motivation, critical thinking, and social skills, such as respect for differing viewpoints, cooperation, and communication. Teachers' individual feedback during group exercises allowed for precise assessment of students' progress. Overall, the study underscored the importance of effective strategies like group learning in fostering comprehensive English language skills development.cal thinking. It also opens up opportunities both academically and professionally, as most scholarly articles are written in English, providing access to a broader range of research and information. Overall, learning English is essential for success in today's interconnected world. English is a highly sought-after skill in the job market due to its role in multinational corporations and communication with diverse cultural backgrounds. Learning English is a holistic development tool that boosts cognitive abilities, personal, academic, and professional growth. Classroom teachers prioritize memorization over critical thinking, while exposure to English- language media enriches personal experiences and deepens connections to the global community. Students who achieve proficiency in English can tap into these resources for further learning.